2014
DOI: 10.1021/ja5017206
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of Highly Enantio- and Diastereoselective Aza-Petasis–Ferrier Rearrangement Catalyzed by Chiral Phosphoric Acid

Abstract: The precise mechanism of the highly anti- and enantioselective aza-Petasis-Ferrier (APF) rearrangement of hemiaminal vinyl ethers catalyzed by a chiral phosphoric acid was investigated by undertaking experimental and theoretical studies. The APF rearrangement is characterized by the following unique mechanistic features: (i) efficient optical kinetic resolution of the starting racemic hemiaminal vinyl ether, (ii) enantioconvergent process from racemic hemiaminal vinyl ethers to optically active β-amino aldehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 99 publications
2
24
0
Order By: Relevance
“…However, whether the reaction benefits from large proximal sterics or small depends on the sterics of the nucleophile. For smaller displaced nucleophiles, large proximal sterics are advantageous, disfavouring Type I E pathways 29, 33, 35, 36, 37, 38, 72, 73, 74, 75, 76, 77, 78. However, if the nucleophile is large, small proximal sterics are essential 32, 34, 39, 79, 80.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, whether the reaction benefits from large proximal sterics or small depends on the sterics of the nucleophile. For smaller displaced nucleophiles, large proximal sterics are advantageous, disfavouring Type I E pathways 29, 33, 35, 36, 37, 38, 72, 73, 74, 75, 76, 77, 78. However, if the nucleophile is large, small proximal sterics are essential 32, 34, 39, 79, 80.…”
Section: Resultsmentioning
confidence: 99%
“…The reactants and the phosphoric acid moiety of the catalyst were included in the high‐layer, and the remaining regions of the catalyst were treated as the low‐layer. This method has previously been shown to give excellent results when used to describe reactions catalyzed by chiral phosphoric acids 4, 16, 18, 34, 35, 36, 37…”
Section: Methodsmentioning
confidence: 99%
“…The authors later disclosed a thorough mechanistic evaluation to further probe this reaction and account for the anomalous temperature effect. 89 They found that the CPA catalyst serves two purposes, acting both as a hydrogen-bond donor to the N -Boc-imine and a hydrogen-bond acceptor from the transient enol. This scaffolding bifunctionality is responsible for both the large degree of anti -selectivity as well as the high enantioselectivities the authors typically observed.…”
Section: Stereoablative Transformationsmentioning
confidence: 99%
“…The advantage of the latter reaction is the formation of ortho-coupled products of phenols and b-naphthol (5 and 6, respectively), whereby the same sort of reactive three-component intermediate TN 2 is generated by reaction of iminium ion II with a nucleophilic carbon center of phenol/naphthol, and subsequent deamination followed by aerobic oxidation generates 10 and 11, respectively. Generation of 12 can be explained by three-component intermediate TN 3 , produced by attack of aryl nucleophile (R À ) on the iminium ion. The aryl nucleophile is generated by the action of OH À on aryl boronic acid.…”
Section: Synthesis Of Benzils By Employing Boronic Acids As Coupling mentioning
confidence: 99%
“…[1] Among different reactions, activation due to secondary-amine-promoted iminium ions has dominated the field and has been exploited in two different directions: 1) reactions, in which amines are used as reagents, such as Mannich, [2] Petasis, [3] and KabachnikFields reactions [4] and 2) iminium-catalyzed reactions, for example, Stork enamine, [5] Knoevenagel, [6] and trans-amination [7] reactions (Figure 1 b). Recently, we established a method based on iminium ions for the synthesis of a-ketoamides.…”
Section: Introductionmentioning
confidence: 99%